A modified optimal control for the mathematical model of dengue virus with vaccination - Pongsumpun, Puntipa; Lamwong, Jiraporn; Tang, I. Ming; Pongsumpun, Puntani (My University, 2023)
The dengue viruses (of which there are four strains) are the causes of three illnesses of increasing severity; dengue fever (DF), dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Recently, dengue fever has reached epidemic proportion in several countries. Strategies or preventative methods have to be developed to combat these epidemics. This can be done by development of vaccines or by preventing the transmission of the virus. The latter approach could involve the use of mosquito nets or insecticide spraying. To determine which strategy would work, we test the strategy using mathematical modeling to simulate the effects of the strategy on the dynamics of the transmission. We have chosen the Susceptible-Exposed-Infected-Recovered (SEIR) model and the Susceptible, Exposed-Infected (SEI) model to describe the human and mosquito populations, repectively. We use the Pontryagin’s maximum principle to find the optimal control conditions. A sensitivity analysis revealed that the transmission rate (ɣℎ, ɣv), the birth rate of human population (µℎ), the constant recruitment rate of the vector population (A) and the total human population (Nℎ) are the most influential factors affecting the disease transmission. Numerical simulations show that the optimal controlled infective responses, when implemented, cause the convergence to zero to be faster than that in uncontrolled cases.
Keywords: dengue; Lyapunov function; mathematical model; optimal control; sensitivity; simulations; stabilities